PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN TWO STAY TWO STRAY DAN JIGSAW PADA MATERI EKOSISTEM DI KELAS X SMA NEGERI 11 MEDAN T.P 2016/2017 - Lia Salvina; Uswatun Hasanah (Universitas Negeri Medan, 2017)
This research aims to determine differences of student learning outcomes that use Two Stay TwoStray and Jigsaw learning models for Ecosystem topic in class X SMA Negeri 11 Medan academic year2016/2017. This type of research is a Quasi Experiment. Sample of the research taken by using randomsampling. The sample consists of 2 classes that are X IPA 6 with 38 students as a Two Stay Two Stray class and XIPA 5 with 38 students too as a Jigsaw class. Instrument that used to collect data is a multiple choices testconsists of 30 questions. The result shows that the average score of student taught by Two Stay Two Straymodel is 80.34 ± 90.4 and is better than those taught by Jigsaw model (75.82 ± 8.69). In this case, t test is usedto test the hypotesis and H0 is rejected tcount > ttable (2.224 > 1.995; Î± = 0.05). Therefore, it can be concludedthat there are differences between student™s score in the Ecosystem topic taught by Two Stay Two Stray andJigsaw models in class X SMA Negeri 11 Medan academic year 2016/2017.Key words: Student™s Score, Two Stay Two Stray, Jigsaw